The Image of Women in Latin American Bourgeoise Mentality: A Reading of Blanca Sol by Mercedes Cabello de Carbonera - Monroy, Leonardo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper interprets the image of women into the bourgeois mentality, based on a reading of Blanca Sol, a novel of the Peruvian writer Mercedes Cabello de Carbonera. This analysis is divided in three main parts: first, there is a comprehension of the way the narrator (an alter ego of the author) observers the bourgeois society and the implications of the social promotion and equality. At the second part, this paper describes how the author of Blanca Sol tries to expose the multiple vicious of this new bourgeois lifestyle, like hypocrisy, abjection and money desire, and how women can be part of the problem but also part of the solution. At last, it is developed an analysis of how in her novel Blanca Sol, Cabello de Carbonera assumes the secularization, one of the most important characteristics of modern society supported by bourgeoisie.